Nano-Resists for Next Generation Semiconductors - FILIP KRZYMIENIECKI (2024)
The incorporation of nanoparticles can improve material characteristics, with their small particle size providing distinctive benefits. Nanocomposite resists in the semiconductor industry can improve feature resolutions on the nanometre scale or etch resistance, with applications including more energy efficient MEMS and novel sensors. This thesis focuses on integrating nickel nanoparticles into photoresists to improve the etch resistance of the material. Increased etch resistance enables the production of deep trenches with nano feature sizes, as well as maintaining samples with even geometry of the structures. The experiments were set up to test the etch resistance of samples with different loading of nickel nanoparticles. Commercially purchased nanoparticles were used for the experiments, as a basis for future use of the nanoparticles produced by MACS (Matrix Assembly Cluster Source) tool. The etch tests were conducted in SPTS systems, an APS (advanced plasma source) tool designed for etching of strongly bonded materials and a DSi-v tool designed for etching Si for vertical sidewalls with the Bosch process. Ellipsometry was used to obtain the differences in thickness pre- and post-etching of the samples, data which was used to calculate the sample etch rates. SEM imaging was used to study the texture of the nanocomposite resists. For the commercially purchased nanoparticle samples, MIR-701 photoresist was used. The results show a positive relationship between the nickel loading and the etch resistance, with an increase of as much as 17% over the control sample. At the structural level, the nanoparticles were integrated into the photoresist successfully, with an even film surface.